2018
DOI: 10.1002/jcsm.12338
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Duchenne muscular dystrophy phenotype following obestatin treatment

Abstract: BackgroundThis study was performed to test the therapeutic potential of obestatin, an autocrine anabolic factor regulating skeletal muscle repair, to ameliorate the Duchenne muscular dystrophy (DMD) phenotype.Methods and resultsUsing a multidisciplinary approach, we characterized the ageing‐related preproghrelin/GPR39 expression patterns in tibialis anterior (TA) muscles of 4‐, 8‐, and 18‐week‐old mdx mice (n = 3/group) and established the effects of obestatin administration at this level in 8‐week‐old mdx mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…A small increase in dystrophin expression is sufficient to reduce levels of biomarkers associated with muscle damage CK, LDH, AST, and ALT are serum enzymes that are elevated in several muscular dystrophies, including DMD, and are widely used in the diagnosis of skeletal muscle injury and damage [29,30]. mdx mice are reported to also have elevated levels of these serum biomarkers compared to WT controls [31,32]. We here confirmed that all four biomarkers were indeed significantly increased in mdx mice treated with the scrambled control compared to WT controls (P < 0.0001) ( Fig.…”
Section: Dosing Results In Higher Dystrophin Levels In Skeletal Mumentioning
confidence: 99%
“…A small increase in dystrophin expression is sufficient to reduce levels of biomarkers associated with muscle damage CK, LDH, AST, and ALT are serum enzymes that are elevated in several muscular dystrophies, including DMD, and are widely used in the diagnosis of skeletal muscle injury and damage [29,30]. mdx mice are reported to also have elevated levels of these serum biomarkers compared to WT controls [31,32]. We here confirmed that all four biomarkers were indeed significantly increased in mdx mice treated with the scrambled control compared to WT controls (P < 0.0001) ( Fig.…”
Section: Dosing Results In Higher Dystrophin Levels In Skeletal Mumentioning
confidence: 99%
“…Similarly, upregulation of utrophin and improvement of the DMD phenotype in mdx mice seems to accompany the reduction of ubiquitin ligase E3 enzymes 51,52 . Utrophin is homologous to dystrophin and also has an affinity for the binding of F‐actin to DGC 53 .…”
Section: Discussionmentioning
confidence: 99%
“…50 Similarly, upregulation of utrophin and improvement of the DMD phenotype in mdx mice seems to accompany the reduction of ubiquitin ligase E3 enzymes. 51,52 Utrophin is homologous to dystrophin and also has an affinity for the binding of F-actin to DGC. 53 Utrophin is upregulated in the mdx mouse, which gives a milder phenotype for this model; however, this upregulation was not observed in patients with DMD.…”
Section: Discussionmentioning
confidence: 99%
“…In previous works, we demonstrated the therapeutic potential of the obestatin/GPR39 system, an autocrine/paracrine system, to regulate skeletal muscle repair [26][27][28][29][30]. Obestatin, a 23-amino acid peptide derived from a polypeptide called preproghrelin, exerts an autocrine anabolic function in skeletal muscle to control the myogenic programme through the G protein-coupled receptor GPR39 [26].…”
mentioning
confidence: 99%
“…In cell transplantation therapy, obestatin not only enhances the e ciency of engraftment but also facilitates an even distribution of myoblasts within the host muscle by enhancing migration [31]. Furthermore, obestatin ameliorate the Duchenne muscular dystrophy phenotype [30]. Interestingly enough, obestatin triggers an up-regulation of the neuromuscular junction (NMJ) genes.…”
mentioning
confidence: 99%